ESTUDO DO COMPORTAMENTO LUMINESCENTE E ELETROQUÍMICO DE UM COMPLEXO METÁLICO VISANDO INTERESSE BIOTECNOLÓGICO - Souza, Priscila; Gonçalves, Alice; Cabeza, Natalia; Macedo, Michile; Dos Anjos, Ademir; Biscoli, Leandro (ANAIS DO ENIC, 2018)
-